THE EFFECT OF THE TALKING STICK TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES OF STUDENTS IN THE SUBJECT OF AQIDAH AKHLAK - Azwar Anas; Sulis Wulansari (Al-Mubin, 2026)
The background of this research is the low learning activity of MI Mathla'ul Anwar students, which is caused by teacher-centered learning, so that students are less active. The purpose of this study is to improve student learning outcomes in the subject of Aqidah Akhlak class V. The research method uses quantitative experimentation with two groups: one model using a cooperative teaching model with a Talking Stick method and the other using the same as in general (conventional). The pretest-posttest research design was one group with a sample of 14 students. Data were collected through questionnaires and documentation, then analyzed by normality and homogeneity tests. The results showed that in the experiment (76.78) the height of the control class was only (68.21), which means that the Alternative Hypothesis was accepted. In conclusion, the application of the Talking Stick-type cooperative learning model can improve student learning outcomes in the Aqidah Akhlak class V subject of MI Mathla'ul Anwar